Recent Synthesis of Nucleoside Phosphonate Analogs Using Olefin Cross-metathesis - Hong, Joon Hee (Current Medicinal Chemistry, 2025)
Nucleotide analogs known as acyclic and cyclic nucleoside phosphonates (ANPs and CNPs, respectively) have a variety of biological properties, including antibacterial, antiviral, antiparasitic, antineoplastic, and immunomodulatory. A strong reaction that has emerged in the last several decades has fundamentally changed our knowledge of the chemistry of nucleoside phosphonates. In particular, Olefin cross-metathesis (CM) has been a potent and practical synthesis route to produce functionalized olefins from essential alkene precursors. This review describes recent synthesis examples of ANPs and CNPs analogs using the Ru-catalyzed olefin cross-metathesis reactions. Olefin cross-metathesis reactions are performed in the olefinic parts of nucleoside and phosphonate produced by Grubbs, Hoveyda-Grubbs, and Nolan. This review presents a synthetic overview of a few chosen nucleosides with biological significance. Their biological activity results are briefly discussed.
Keywords: cyclic nucleoside phosphonates